(untitled) (Scientific journal of the Fergana State University, 2025)
Tillage is one of the main and most widely used methods of human impact on the soil. Its purpose is to create favorable heat, water, air and biological regimes for the plant, thereby increasing its productivity and helping to mobilize nutrient resources, as well as fight against weeds and soil erosion. Deep softening allows the root system to develop not in compacted horizons, as in normal conditions, but in a softer soil layer, that is, in an environment with sufficient air and moisture penetration.